Asymmetric blade disc turbine for high aeration rates - Bombač, Andrej (Strojniški vestnik, 2018)
This paper presents some fluid-dynamic characteristics of modified impellers for air dispersion with high flow rates. An asymmetrically folded blade turbine (ABT) was developed as the last in a series of research studies on modified blades of disk impellers, such as twisted blade turbine (TBT) and other blade shape turbines. The analyses of the modified impeller characteristics in a model scale mixing device includes the measurements of: a) the mixing power in liquid stirring and in the air dispersion up to the occurrence of flooding, b) global gas hold up, c) appearance of flooding, and d) the mixing times in liquid stirring. The energy dissipation of the ABT impeller was found to be very small, in the range of hydrodynamic regimes in industrial scale operations with a power number equal to PoABT ~ 1.75. During aeration in water, the ABT impeller has a very small power draw reduction (less than 16 %) at the same stirrer speed (corresponding to Fr = 0.3) and is capable of dispersing substantially higher amounts of air (up to 53 %) than the Rushton turbine is, as well as achieving shorter mixing times. While local mixing time expresses only changes with the time at the measuring location, a CFD analysis was included for better insight into inhomogeneity in the liquid. To compare the efficacy of the ABT impeller with other impellers, some results of our previous research are summarized.
Keywords: ABT impeller; ABT mešalo; air dispersing; čas pomešanja; dispergiranje zraka; flooding; gas holdup; liquid mixing; mešanje kapljevine; mixing time; poplavno stanje; prirastek plinaste faze